THE EFFECT OF PHYSICAL EDUCATION AND SPORT ON FITNESS STATUS of UNIVERSITY STUDENTS - Pucsok, József Márton; Balogh, László; Ráthonyi, Gergely; Varga, Katalin; Bíró, Eszter; Perényi, Gabriella; Lenténé Puskás, Andrea (Stadium - Hungarian Journal of Sport Sciences, 2020)
The physical fitness state of university students has deteriorated over the years. Relevant data is needed to investigate this tendency thoroughly. We conducted a longitudinal examination among university students in Debrecen, Hungary. At the first stage of our examinations, we examined sixty male and female participants to assess their physical fitness status. They participated in four different activities (pilates, spinning, wellness-general fitness, body-shaping) once a week. Each exercise session lasted for 90 minutes. We conducted a pre-and post-exercise screening, which consisted of a Beep-test, push-up, and sit-up tests.  We hypothesized that the different types of activities might alter the exercise response. Aerobic performance, upper-body, and abdominal strength may differ depending on the type of exercise—international recommendations suggesting that 150 minutes of physical activity is necessary for physical fitness benefits. Our results demonstrated that 90 minutes of exercise might significantly improve inactive young adults' physical fitness state once a week.